2008
DOI: 10.1021/es703016v
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine as Precursor to Secondary Organic Aerosol Formation via Nitrate Radical Reaction in the Atmosphere

Abstract: Amines in fine particulate matter have been detected and quantified during ambient studies of winter inversions in Logan, UT, using aerosol mass spectrometry. Amine-related compounds account for 0.5-6 microg m(-3) of fine particulate mass during some wintertime periods. The amine contributions sometimes show a clear diurnal pattern, reaching peak concentrations during the middle of the nightwhile decreasing during the morning and afternoon. Smog chamber reactions show that the reaction of tertiary amines with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 43 publications
2
95
0
5
Order By: Relevance
“…In addition to the peak at mass-to-charge þ59 corresponding to the TMA, dominant peaks in the positive ion mass spectrum are potassium/organics (Dall'Osto et al, 2009a;Moffet et al, 2008). In this study, no evidence showed the presence of non-salt organic products of TMA in particles because no fragments of common secondary organic products for TMA such as trimethylamine-Noxide at m/z 76 [TMAOH] þ , dimethylnitramine at m/z À90 [CH 3 N 2 O 2 ] À and m/z À74 [CH 3 N 2 O] À were observed through the whole sampling period (Angelino et al, 2001;Silva et al, 2008). Fig.…”
Section: Detection Of Tma-containing Particles With Spamsmentioning
confidence: 58%
See 3 more Smart Citations
“…In addition to the peak at mass-to-charge þ59 corresponding to the TMA, dominant peaks in the positive ion mass spectrum are potassium/organics (Dall'Osto et al, 2009a;Moffet et al, 2008). In this study, no evidence showed the presence of non-salt organic products of TMA in particles because no fragments of common secondary organic products for TMA such as trimethylamine-Noxide at m/z 76 [TMAOH] þ , dimethylnitramine at m/z À90 [CH 3 N 2 O 2 ] À and m/z À74 [CH 3 N 2 O] À were observed through the whole sampling period (Angelino et al, 2001;Silva et al, 2008). Fig.…”
Section: Detection Of Tma-containing Particles With Spamsmentioning
confidence: 58%
“…Recent measurements by Silva et al (2008) showed that amines could account up to 20% of organic matter mass in fine aerosol during some wintertime periods in Utah, USA. Angelino et al (2001) reported that up to 80% of single particles contained amine signals during some episodes in Riverside, CA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can also undergo photooxidation and oxidation reactions with OH radicals, NO 3 radicals and O 3 in the ambient atmosphere to form non-volatile aerosol components. [13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events.…”
Section: Introductionmentioning
confidence: 99%